LITTERING BEHAVIOR: PSYCHOLOGICAL AND ECOLOGICAL PERSPECTIVES - Nadhin Hasthi Awliya; Raffi Asraf; Naufal Ramadhan Purba; Cantika Anindya Putri Desky; Reza Harapenta Ginting (MEDALION JOURNAL: Medical Research, Nursing, Health and Midwife Participation, 2025)
Littering behavior is a form of antisocial action that has a negative impact on the environment and reflects the psychological dynamics of individuals. This article explores the relationship between this behavior and human disconnection from nature, ecological awareness, and psychological dimensions such as existential fear. With an environmental psychology approach, this article discusses how irresponsible behavior towards the environment can be overcome by increasing ecological awareness and strengthening the relationship between humans and nature.